Sosialisasi Penerapan Peraturan K3 (Keselamatan dan Kesehatan Kerja) Pada Siswa SMA di Kabupaten Solok Selatan Sumatera Barat - Boy, Wendi; Herman, Hazmal; Irawan, Bayu Budi; Mazni, Deni Irda; Vitri, Gusni; Zayu, Wiwin Putri; Wahyudi, Dicky; Iqbal, Iqbal; Hanif, Hanif (LPPM Universitas Dharma Andalas, 2024)
Occupational Safety and Health (K3) is a form of effort to create a workplace that is safe, healthy, free from environmental pollution, so that it can protect and be free from work accidents, ultimately increasing work efficiency and productivity. Schools are responsible for keeping the environment clean, beautiful and orderly so that a conducive learning environment can be created. Therefore, schools are also required to have professional staff who understand and are competent in the field of K3. The aim of this service is to provide knowledge to high school students in South Solok Regency so that they care more about K3 in their respective school environments. This service found that there was still low awareness of K3 among teachers and high school students in South Solok Regency, it was recorded that the cleanliness of toilets and bathrooms was very lacking in each school, school cleanliness was very lacking, awareness of the use of PPE when driving two-wheeled students was very lacking. especially wearing a helmet. There is a need for guidance in schools, especially for these students, especially regarding K3 culture in schools.